Кинематика свободнообкатного резания при обработке наружной сферической поверхности - Добровольский, А. В.; Краснощек, Ю. С. (НТУ "ХПІ", 2009)
Аналіз кінематики вільнообкатувального різання показав, що на окремих ділянках дуги контакту різця і заготовки швидкість різання може приймати додатне і від'ємне значення. При додатному значенні швидкості різання відбувається знімання матеріалу, при від'ємному – вигладжування.

The analysis of kinematic soffreely rolled cutting displayed that at certain sections of the contact are both of cutter and material treated, the cutting speed can gain positive and negative values. Treated material is removed under the conditions of cutting speed, butin the case of negative value of cutting speed-smothing is occurred.
Keywords: метод финишной обработки; сложнопрофильные поверхности; режущая кромка; круговая подача